PET and PET/CT Study Guide A Review for Passing the PET Specialty Exam - Moniuszko, Andrzej; Sciuk, Adam.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
The PET and PET/CT Study Guide presents a comprehensive review of nuclear medicine principles and concepts necessary for passing PET specialty board examinations. The practice questions and content are similar to those found on the Nuclear Medicine Technology Certification Board (NMTCB) exam, allowing test takers to maximize their chances of success. The book is organized by test sections of increasing difficulty, with over 650 multiple-choice questions covering all areas of positron emission tomography, including radiation safety; radionuclides; instrumentation and quality control; patient care; and diagnostic and therapeutic procedures. Detailed answers and explanations to the practice questions follow. Supplementary appendices include common formulas, numbers, and abbreviations, along with a glossary of terms for easy access by readers. The PET and PET/CT Study Guide is a valuable reference for nuclear medicine technologists, nuclear medicine physicians, and all other imaging professionals in need of a concise review of the basics of PET and PET/CT imaging.
Tackling the Multiple-Choice Test -- Practice Test #1 (Easy) -- Practice Test #2 (Moderate) -- Practice Test #3 (Hard) -- Practice Test #4 (Bonus Questions) -- Appendix A: Numbers and Formulas -- Appendix B: Commonly Used Abbreviations and Symbols in Nuclear Medicine -- Appendix C: Glossary -- Appendix D: Useful Web Sites -- Appendix E: Figure Answer Key.
Keywords: Medicine; Radiology, Medical; Nuclear medicine; Medicine & Public Health; Nuclear Medicine; Imaging / Radiology